PEDF improves atherosclerotic plaque stability by inhibiting macrophage inflammation response. (15th May 2017) - Wen, Hao; Liu, Minghao; Liu, Zhaoqiang; Yang, Xiaoyan; Liu, Xiaoling; Ni, Mei; Dong, Mei; Luan, Xiaorong; Yuan, Yan; Xu, Xinsheng; Lu, Huixia
Abstract: Background: Atherosclerosis is a vascular disease with plaque formation and growth. Instable plaque with chronic inflammation is closely related to adverse cardiac outcomes. Pigment epithelium-derived factor (PEDF) is an endogenous multifunctional cytokine that possesses the ability of anti-inflammation. The aim of this study is to detect whether PEDF has protective effect on the stability of atherosclerotic plaque and to explore whether the effect of anti-inflammation involved. Methods and results: ApoE −/− mice fed with high fat diet and RAW264.7 cells were used to evaluate anti-inflammatory activities of PEDF both in vivo and in vitro . PEDF overexpression improved atherosclerotic plaque stability in ApoE −/− mice. The expression of inflammatory factors (interleukin-1β [IL-1β], interleukin-6 [IL-6], tumor necrosis factor-α [TNF-α], monocyte chemotactic protein-1 [MCP-1] and matrix metalloproteinase [MMP-9]) was significantly decreased with PEDF overexpression in vivo and in vitro . The anti-inflammation effect of PEDF was attenuated by PPAR-γ specific antagonist GW9662. In addition, PEDF significantly decreased the expression of phosphorylated ERK-MAPK, p38-MAPK and JNK-MAPK. GW9662 partly reversed the PEDF-mediated depression of phosphorylated ERK- and p38-MAPK but has no significant effect on JNK-MAPK. Conclusions: PEDF has protective effect on increasing AS plaque stability through ameliorating macrophage inflammation. PPAR-γ and downstream MAPKs were involved in the mechanism.